2015
DOI: 10.1103/physrevb.92.115101
|View full text |Cite
|
Sign up to set email alerts
|

Many-body effects and ultraviolet renormalization in three-dimensional Dirac materials

Abstract: We develop a theory for electron-electron interaction-induced many-body effects in threedimensional Weyl or Dirac semimetals, including interaction corrections to the polarizability, electron self-energy, and vertex function, up to second order in the effective fine structure constant of the Dirac material. These results are used to derive the higher-order ultraviolet renormalization of the Fermi velocity, effective coupling, and quasiparticle residue, revealing that the corrections to the renormalization grou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 84 publications
(125 reference statements)
6
82
0
Order By: Relevance
“…Generating 2D semi-Dirac fermions by merging pairs of Dirac points was predicted to take place in deformed graphene [102][103][104][105][106], pressured organic compound α-(BEDT-TTF) 2 I 3 [104,[106][107][108], few-layer black phosphorus subject to pressure or perpendicular electric field [109,110] or doping [111], and some sorts of artificial optical lattices [112,113]. Experimentally, the merging of distinct Dirac points and the appearance of semi-Dirac fermions were recently observed in ultracold Fermi gas of 40 K atoms in honeycomb lattice [114], and microwave cavities with graphene-like structure [115]. Kim et al [116] realized semi-Dirac semimetals in few-layer black phosphorus at critical surface doping with potassium.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generating 2D semi-Dirac fermions by merging pairs of Dirac points was predicted to take place in deformed graphene [102][103][104][105][106], pressured organic compound α-(BEDT-TTF) 2 I 3 [104,[106][107][108], few-layer black phosphorus subject to pressure or perpendicular electric field [109,110] or doping [111], and some sorts of artificial optical lattices [112,113]. Experimentally, the merging of distinct Dirac points and the appearance of semi-Dirac fermions were recently observed in ultracold Fermi gas of 40 K atoms in honeycomb lattice [114], and microwave cavities with graphene-like structure [115]. Kim et al [116] realized semi-Dirac semimetals in few-layer black phosphorus at critical surface doping with potassium.…”
Section: Introductionmentioning
confidence: 99%
“…The role of Coulomb interaction depends crucially on the fermion dispersion and the dimension. Extensive renormalization group (RG) analysis [53] have revealed that Coulomb interaction is marginally irrelevant in 2D Dirac semimetal [5,36,37], 3D Dirac/Weyl semimetal [38][39][40][41], and also 3D double Weyl semimetal [49,50]. The Fermi liquid (FL) theory is valid in 2D Dirac semimetal [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the renormalization group (RG) theory it is possible to express the interacting compressibility at one density (i.e., one k F value) simply in terms of that at another density, thus completely eliminating the unknown ultraviolet scale associated with k c as has been extensively discussed recently in Ref. 60 . Note that the interaction coupling constant α = e 2 /(κv F ) is the ratio of the interaction to kinetic energy (the effective fine-structure constant), which is density independent for Dirac materials.…”
Section: Finite-temperature Compressibilitymentioning
confidence: 99%
“…60 . A practical way to compare theory with experiment would be to eliminate k c and express the experimental compressibility at one density with that at another density.…”
Section: Finite-temperature Compressibilitymentioning
confidence: 99%